THE ROLE OF OPINION LEADERS IN PARTICIPATORY DEVELOPMENT COMMUNICATION OF FORMER MIGRANT WORKERS - Meria Octavianti; Slamet Mulyana; Dadang Sugiana; Kimiyati El Karimah; Aang Koswara (Universitas Bunda Mulia, 2021)
The phenomenon of migrant workers has been a social problem that has to be solved by many stakeholders. This is that it greatly impacts economy, family, law, and other aspects of community. This study seeks to reveal how participatory development communication is applied in the empowerment of Indonesian former migrant workers. This study employed qualitative method with case study approach because its aim was to generate holistic, systemic description and reveal the meaning of empirical facts about participatory development communication in empowering the Indonesian former migrant workers (PMI). Data were collected through interviews with five key informants of community leaders and sources of relevant agencies as well as direct observations. The study found: (1) Forum of Indonesian Former Migrant Workers (Forum Purna PMI) seeks to empower the economy of former migrant workers in Desa Celak; (2) Community participation in Desa Celak, particularly among former migrant workers, is considered well-conducted; and (3) Local public figures as opinion leaders hold a significant role in encouraging the community in village development.